2006
DOI: 10.1007/s10489-006-8517-4
|View full text |Cite
|
Sign up to set email alerts
|

State-based modelling in hazard identification

Abstract: The signed directed graph (SDG) is the most commonly used type of model for automated hazard identification in chemical plants. Although SDG models are efficient in simulating the plant, they have some weaknesses, which are discussed here in relation to typical process industry examples. Ways to tackle these problems are suggested, and the view is taken that a state-based formalism is needed, to take account of the discrete components in the system, their connection together, and their behaviour over time. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Model-based methods for fault diagnosis have been reviewed by Venkatasubramanian et al , To support qualitative model-based monitoring and emergency planning, a modeling methodology that can support causal and consequential reasoning is needed. Several such systems have been suggested; one particularly popular form is the signed directed graph, which is qualitative; however, often the knowledge representation used is structure-centered rather than functionality-centered. Another class of graphsbond graphsconstitute an interesting originally quantitative graphical representation of a physical dynamic system that covers multiple energy domains seamlessly.…”
Section: Application Of Functional Conceptsmentioning
confidence: 99%
“…Model-based methods for fault diagnosis have been reviewed by Venkatasubramanian et al , To support qualitative model-based monitoring and emergency planning, a modeling methodology that can support causal and consequential reasoning is needed. Several such systems have been suggested; one particularly popular form is the signed directed graph, which is qualitative; however, often the knowledge representation used is structure-centered rather than functionality-centered. Another class of graphsbond graphsconstitute an interesting originally quantitative graphical representation of a physical dynamic system that covers multiple energy domains seamlessly.…”
Section: Application Of Functional Conceptsmentioning
confidence: 99%
“…However, they do not allow a flexible enough representation of the alternative operating sequences which arise from deviations from intended operations, or where some part of the plant is modified. McCoy et al [28] have considered the use of Petri nets in hazard identification systems. They found that if the order of two operating instructions is exchanged, or if a new equipment item is added to the plant, it is very difficult to modify the Petri net to take account of this.…”
Section: Expert Systemsmentioning
confidence: 99%